KMHD UBG Mengabdi: Pemanfaatan Tanaman Obat Keluarga sebagai Health Maintenance pada Masyarakat Penyakit Kronis - Aji Kresnapati, Nyoman Bagus; Indriani, Nurul; Satria Wirananda, I Nengah (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The aim of this activity is to educate residents about the use of Tanaman Obat Keluarga (TOGA) and honey as self-medication in Batu Kumbung Village, Narmada District, West Lombok, NTB. The method of this activity is Komunikasi, Informasi dan Edukasi (KIE) based on Participatory Action Research (PAR), which is a socialization approach using active community participation which aims to explore problems such as health checks for BMI, blood pressure and glucose and from these results, a solution is implemented, namely KEI TOGA and honey to the community. The results of the activity showed that the average age of the community was 36 years, BMI 21.08% (normal 17-25%), blood pressure 119/75 mmHg (normal <130 mmHg), glucose level 95 mg/dL (normal <150 mg/dL), it was concluded that the average health status of the community was in the normal category. The implication of this activity is the community's active role so that this activity is successful and the community receives TOGA education as a self-medication treatment.